Maritime India - Nayyar, K. K. (Kewal Krishan) (New Delhi : Rupa & Co. in association with National Maritime Foundation, 2005)
Contributed articles.
Includes bibliographical references and index.
Keywords: Sea-power -- India; National security -- Indian Ocean Region; Indian Ocean -- Strategic aspects